ANALYSIS OF MUSIC FORM AND CELLO PLAYING TECHNIQUES SONATINE FOR CELLO & PIANO BY BUDHI NGURAH - Adi William Raharja (Universitas Negeri Surabaya, 2020)
This resesarch aims to describe the musical form, and cello techniques that include fingering and bowing techniques in the work of Budhi Ngurah. The research process is using descriptive analytic methods. Data in this research were obtained by observation, interviews, and documentation. And analyzed by reduction, presentation and inference. The results indicate that the Sonatine For Cello and Piano by Budhi Ngurah consists of 3 movements. Movement I has a sonata forms with moderate tempo consisting of exposition, development, and recapitulation. Movement II has a three parts music form, ABA. Movement III has a rondo music form. The cello playing technique in this repertoar is important for performance which includes tone color, phrase of the music, and interpretation.